2010
DOI: 10.1111/j.1365-2265.2009.03706.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of octreotide exposure during pregnancy in acromegaly

Abstract: Short-acting octreotide appears not to affect the function of the maternal-foetal barrier or foetal development, except for the occurrence of acute, reversible, and clinically irrelevant haemodynamic changes. These data support the feasibility and safety of treatment with short-acting octreotide in acromegalic women during pregnancy and excludes major matters of concern about the effects of this medication on pregnancy itself and its outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…Newborns from women who interrupted medical treatment before or at the beginning of pregnancy have been typically normal (2,3,4,5,38). Also, children born from women with acromegaly who discontinued treatment during pregnancy have been shown to have normal general health status at 2, 3 and 6 years of age (73,74,75), as well as IQ scores similar to those born from normal women or from women with prolactinoma (76). However, as some patients with acromegaly may have or develop impaired glucose tolerance/diabetes mellitus and hypertension during pregnancy, their newborns should also be considered at a higher risk for macrosomia and microsomia (77) respectively.…”
Section: Effect Of Acromegaly and Its Treatment On Fetal Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Newborns from women who interrupted medical treatment before or at the beginning of pregnancy have been typically normal (2,3,4,5,38). Also, children born from women with acromegaly who discontinued treatment during pregnancy have been shown to have normal general health status at 2, 3 and 6 years of age (73,74,75), as well as IQ scores similar to those born from normal women or from women with prolactinoma (76). However, as some patients with acromegaly may have or develop impaired glucose tolerance/diabetes mellitus and hypertension during pregnancy, their newborns should also be considered at a higher risk for macrosomia and microsomia (77) respectively.…”
Section: Effect Of Acromegaly and Its Treatment On Fetal Developmentmentioning
confidence: 99%
“…Although octreotide crosses placental barrier and placenta has somatostatin receptors that bind octreotide (78), no serious adverse fetal outcomes have been detected in nearly 50 (2,3,4,5,7,36,38,47,48,50,51,55,57,63,79,80,81,82,83,84) cases of transient exposure (mostly in first trimester) nor in a much smaller number of continuous exposure to somatostatin analogs (SA) and/or dopaminergic agonists (4,64,73,75,78,85,86,87). Notwithstanding, concerns about low birth weight associated to fetal exposure to SA either alone or, as more often reported, in combination with dopaminergic agonists (DA) have been raised by a large retrospective study and by few case reports (3,4,85,88).…”
Section: Effect Of Acromegaly and Its Treatment On Fetal Developmentmentioning
confidence: 99%
“…Octreotide crosses the placental barrier, is present in maternal milk, and has been shown to decrease fetal size (14). Cabergoline, on the other hand, is considered safe during pregnancy (15), but impairs lactation.…”
Section: Obstetrical/fetal Outcomes and Lactationmentioning
confidence: 99%
“…With the widespread use of pharmacological treatment to control disease activity, a consensus on acromegaly management has recently stated the need to encourage reporting of outcomes in medically treated pregnant patients (13). During pregnancy, pharmacological treatment with somatostatin analogs has been associated with decreased length in newborns (14), whereas cabergoline has been considered probably safe in prolactinomas (15), and pegvisomant, a GH receptor antagonist, has been reportedly used in only two cases (16,17). Although cessation of medical therapy during pregnancy has been usually advised (13), this recommendation results primarily from the lack of a large database on drug safety and not from prospective studies on pregnancy outcomes following drug withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, medical treatment with SA during pregnancy was associated with low birth weight. It has been reported that octreotide crosses placenta (21,22), and therefore, it may potentially affect the fetal outcome. Nevertheless, based on the lack of sufficient data on the safety of SAs during pregnancy, it is generally recommended to limit their usage during pregnancy in symptomatic patients (4).…”
Section: Discussionmentioning
confidence: 99%